The Noel letters - Evans, Richard Paul (New York : Gallery Books, 2020)
Returning to her childhood home after nearly two decades and reeling from upheavals in her world, Noel Post inherits her father's bookstore and begins receiving letters from an anonymous source, each one containing thoughts and lessons about her life and her future, and as she begins to reacquaint herself with the bookstore and the people she left behind, Noel starts to unravel the reality of her painful childhood and the truth about her family.
Keywords: Letters -- Fiction; Bookstores -- Fiction; Christmas fiction